Designing a conceptual model of the geospatial database for hazardous animal burial sites affected by anthrax - Moskalenko, A.; Ievsiukov, T. (Land Management, Cadastre and Land Monitoring, 2025)
The article presents the author's approach to the systematization and accumulation of geospatial and attributive data on dangerous burials of animals that died from anthrax. Anthrax is a zoonotic disease, the spores of which can remain viable in the soil for decades, posing a potential threat. Burials of animals not carried out in biothermal pits (mainly before 1954) do not provide an adequate level of safety. In the event of a shift in the soil cover, spores can reach the surface and cause new cases of the disease among wild and domestic animals, as well as infection of people. A significant part of such burials does not have clearly established boundaries of land plots and established regimes of limited use of adjacent territories, which complicates control over their condition.As part of the study, the available geospatial and attributive data on dangerous burials were structured, and a conceptual model of a geospatial database was developed, which ensures the accumulation, structuring, and systematization of data. The model is built using UML notation and is presented in the form of a class diagram that reflects the main structural elements of the database and their attributes.The results obtained can be used to create a physical model of a geospatial database for the registration (register) of lands with dangerous burials of animals that died from anthrax, as well as for the further development of the monitoring system, planning of sanitary and protective measures, establishing regimes of limited land use, etc.Keywords: geospatial database, conceptual model, anthrax.
Keywords: geospatial database; conceptual model; anthrax